Structural Health Monitoring of a Tall Building during Construction with Fiber Bragg Grating Sensors. (17th October 2012) - Li, D. S.; Ren, L.; Li, H. N.; Song, G. B.
Abstract : Fiber Bragg grating sensors demonstrate a great potential as a structural health monitoring tool for civil structures to ensure structural integrity, durability, and reliability. The advantages of applying fiber optic sensors to a tall building include their immunity to electromagnetic interference and their multiplexing ability to transfer optical signals over a long distance. In the work, fiber Bragg grating sensors, consisting of strain and temperature sensors, are applied to structural monitoring of an 18-floor tall building since the date of its construction. The strain transferring rate from host material to the fiber core is discussed and the calibration of packaged fiber Bragg grating sensor is presented. The main purposes of the investigation are monitoring temperature evolution history within concrete during the pouring and curing process, measuring variation of the main column strains on the underground floor while upper 18 floors were subsequently added on, and monitoring relative displacement between two foundation blocks. Fiber Bragg grating sensors have been installed and integrated continuously for more than five months. Monitoring results of temperature and strain are presented in the paper. Furthermore, temperature lag behavior between concrete and its surrounding air is investigated.